Spenser and literary pictorialism - Bender, John B. (Princeton University Press, 1972)
Focusing, framing, scanning-the language of film-and Gombrich's studies in the psychology of perception are used by John Bender to isolate pictorial effects and devices in literature. The theory that he proposes, grounded in his analysis of Spenser, "the painter of poets," discriminates between the descriptive and the pictorial in poetry.Originally published in 1972.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Keywords: Spenser, Edmund, -- 1552?-1599 -- Technique.; Spenser, Edmund, -- 1552?-1599; Ut pictura poesis (Aesthetics); Description (Rhetoric) -- History -- 16th century.; Ut pictura poesis (Esthétique); Discours descriptif -- Histoire -- 16e siècle.; ut pictura poesis.; POETRY -- European -- English, Irish, Scottish, Welsh.; POETRY -- English, Irish, Scottish, Welsh.; Description (Rhetoric); Technique; 1500-1599; History